Modeling for determinants of human trafficking - Seo-Young Cho (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2012)
This study aims to identify robust push and pull factors of human trafficking. I test for the robustness of 78 push and 67 pull factors suggested in the literature. By employing an extreme bound analysis, running more than two million regressions with all possible combinations of variables for up to 180 countries during the period of 1995-2010, I show that crime prevalence robustly explains human trafficking prevalence both in destination and origin countries. My finding also implies that a low level of gender equality and development may have constraining effects on human trafficking outflows, contrary to expectations. The linkage between migration and human trafficking is less clear, and institutional quality matters more in origin countries than destinations.
Keywords: F22; J16; J61; O15; 330; human trafficking; push and pull factors; robustness; extreme bound analysis; Menschenhandel; Kriminalität; Gleichberechtigung; Entwicklungsstufe; Schätzung; Welt